Criminogenic and Non-Criminogenic Factors and Their Association With Reintegration Success for Individuals Under Judicial Orders in Canada - Jung, Sandy (International journal of offender therapy and comparative criminology, 2025)
Justice-involved individuals who reach the end of their full prison sentence no longer benefit from the supervision and rehabilitation services offered by probation or parole. Some of these individuals, who have been assessed to be a high risk for sexual and violent reoffending and deemed to pose a significant violence risk in the community if released, are placed on a judicial order in Canada, and police are asked to supervise and manage the risk of these individuals. In the current study, the files of 45 high-risk, justice-involved individuals, who completed their sentences, were released from a Canadian prison into the province of Alberta, and supervised by police under a judicial order, were reviewed for the presence of criminogenic and non-criminogenic needs over the first year of release. The associations between these needs and proximal reintegration outcomes were examined. Our findings revealed that basic needs and responsivity issues were prevalent in the early part of supervision; however, these factors were unrelated to proximal reintegration success. In contrast, criminogenic needs were prevalent and associated with poorer reintegration. This study reinforces the role that police can play in monitoring and addressing criminogenic needs with the goal of reducing recidivism and employing the help of non-police supports to address non-criminogenic needs.